Water reclamation and reuse using vis-light responsive novel photocatalyst - Chen, Wenjie (2013)
Graphene oxide (GO) was synthesized through a modified Hummers method and was evaluated through characterization with various techniques (i.e. XRD, Raman, TGA, FTIR, XPS, TEM). The as–prepared GO, together with titanium butoxide, cetyltrimethylammonium bromide (CTAB) and AgNO3, were used as starting materials to develop a novel four–component nanocomposite, Ag–AgBr/TiO2/reduced graphene oxide (RGO), through a facile solvothermal–photoreduction approach. Evidence of GO reduction to RGO was confirmed with Raman, FTIR and XPS analysis. The as–prepared nanocomposites were systematically evaluated for degradation of common water pollutants, such as penicillin (PG), sulfanilamide (SNM), carbamazepin (CBZ) and tetracycline (TC), in a batch photoreactor under white light–emittting diode (LED–W) irradiation. Compared to the single–component (TiO2), two–component (Ag–AgBr and Ag/TiO2) and three–component (Ag–Ag/RGO–1 and Ag–AgBr/TiO2), the heterogeneous four–component nanocomposite (Ag–AgBr/TiO2/RGO–1, with mass ratio of GO to TiO2 at 1%) exhibited the highest photocatalytic performance. Ag–AgBr/TiO2/RGO–1 achieved 98% of PG degradation after 2 h irradiation which was higher than those of 96% and 91% achieved by Ag–AgBr/TiO2/RGO–5 and Ag–AgBr/TiO2/RGO–10 respectively. The photocatalytic evaluation coincides with the occurrence of the distinct charge transfer contributed by the well–dispersed nanojunctions between Ag–AgBr and TiO2. Furthermore, PL intensity increased with increasing RGO content, which suggests that excessive RGO could promote recombination of photo–generated electrons and holes. The enhanced action spectrum of Ag–AgBr/TiO2/RGO–1 was exhibited under different visible–light sources. It demonstrated the ability of Ag–AgBr/TiO2/RGO–1 to achieve photocatalytic activities under visible light source, with wavelength at ca. 600 nm. The invisible light photocatalytic behaviour could be induced by the surface plasmon resonance effect of Ag nanoparticles and the enhanced visible–light absorption exhibited by AgBr. The performance of Ag–AgBr/TiO2/RGO–1 suspension in a continuous flow through hybrid submerged photoreactor (sMPR) was also studied. After 2 h of irradiation, it yielded 98% PG photocatalytic degradation efficiency. With the permeate turbidity kept <0.2 NTU, the submerged hollow fiber polyvinyldene fluoride (PVDF) microfiltration (MF) membrane module showed good photocatalyst recovery. The high recovery efficiency could be attributed to the average particle size of the Ag–AgBr/TiO2/RGO–1 suspension, which is larger than that of the MF membrane pore size (0.1 μm). Compared with the case without backwashing operation, the 10 min interval backwashing operation significantly reduced the transmembrane pressure (TMP), while improving the PG photodegradation.